Enhancing sludge dewatering efficiency through bioleaching facilitated by increasing reactive oxygen species. (1st March 2023) - Li, Ting; Yang, Jiawei; Zhou, Yujun; Luo, Yixin; Zhou, Bo; Fang, Di; Li, Jiansheng; Zhou, Lixiang
Highlights: The increase of radicals in sludge bioleaching promoted sludge dewatering efficiency. 90.3% SRF reduction appeared in BS+H2 O2 process after only 30 min reaction. Radicals oxidation and Fe 3+ flocculation had a synergistic effect. A. ferrooxidans LX5 and H2 O2 had significant contribution to Fe 3+ production. Abstract: Bioleaching facilitated by iron-oxidizing bacteria is regarded as a promising sludge dewatering method due to excellent dewaterability and low cost. However, a two-days bioleaching time for sludge conditioning decreased its daily treatment capacity. In fact, Fe 2+ easily reacts with O2 to produce reactive oxygen species (ROS) with high oxidizing activity. Can bioleaching performed in Fe 2+ -rich system generate ROS to decompose sludge extracellular polymeric substances (EPS)? Here both contribution of ROS produced in bioleaching to improve sludge dewaterability and the increase of ROS content to shorten sludge bioleaching treatment time were investigated. The introduction of H2 O2 in sludge bioleaching treatment (BS+H2 O2 ) to increase ROS could simultaneously improve sludge dewaterability and decrease bioleaching time. Specific resistance to filtration (SRF) and capillary suction time (CST) reduction ratios (90.3% and 80.9%) in BS+H2 O2 process were much higher than those in other processes after only 30 min reaction. Mechanisms of improving sludge dewaterability in BS+H2 O2 mainly included ROS oxidation and Fe 3+ flocculation by analysis of the contribution factors. These findings not only provide an effectively method to promote sludge dewatering efficiency of bioleaching, but also give new sights into the design of cost-efficient processes for improving the sludge dewatering. Graphical abstract: Image, graphical abstract